KUTKM Tubuh Klinik Pelajar - Safei, Su'aidi (KUTKM, 2004)
National Technical University College of Malaysia (KUTKM) has set up a clinic for students providing health services to all students. It can reduce cases of sick students waiting too long for treatment at the hospital and save the cost of health care expenses.